(untitled) (RR Interdisciplinary Journal, 2024)
Chemical fertilizers and pesticides are widely used in agriculture to boost productivity. However, their extensive application poses significant socio-economic and environmental challenges. Sustainable agricultural practices are essential for addressing poverty, protecting environmental quality, and achieving global sustainable development goals. This study examined the socio-economic and environmental impacts of pesticide and fertilizer use in Changunarayan Municipality, Nepal. It focused on health and environmental risks as well as the awareness levels of farmers. A descriptive research design was employed, integrating primary and secondary data, with purposive sampling of 120 households. Data collection involved structured questionnaires, interviews, checklists, and field observations. Quantitative data were analyzed statistically, while qualitative data were interpreted descriptively. The findings reveal that while chemical inputs have improved agricultural productivity, they significantly threaten soil health, water quality, and human health. Over 71% of surveyed farmers reported health issues related to pesticide exposure. The study underscores the urgent need for sustainable alternatives, such as organic farming and Integrated Pest Management (IPM), to mitigate these adverse effects and promote long-term ecological and economic sustainability. agriculture